Respuestas
Respuesta dada por:
2
3x + 2y =17
3x - 2y = 1
Simplicamos y nos queda:
3x + 3x = 18
6x = 18
x = 3
y = 4
Por lo tanto:
x - y / y
= 3 - 4 / 4
= -1/4
RPTA.: -1/4 alternativa "A"
3x - 2y = 1
Simplicamos y nos queda:
3x + 3x = 18
6x = 18
x = 3
y = 4
Por lo tanto:
x - y / y
= 3 - 4 / 4
= -1/4
RPTA.: -1/4 alternativa "A"
Respuesta dada por:
1
6x=17
x=18/6 ; x=3
remplazando en la ecuacion 3x-2y= 1
3(3)-2y=1
-2y= 1-9
-2y= -8
y= 4
el valor de (x-y)/y = (3 - 4)/4 = -1/4
x=18/6 ; x=3
remplazando en la ecuacion 3x-2y= 1
3(3)-2y=1
-2y= 1-9
-2y= -8
y= 4
el valor de (x-y)/y = (3 - 4)/4 = -1/4
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años